Building the rule of law for maritime security in China: a domestic law perspective - Li, Weihai (Frontiers in Marine Science, 2024)
Maritime security is an essential component of national security, and the effective maintenance of China’s maritime security urgently needs a complete guarantee of the rule of law. Since the founding of the People’s Republic of China in 1949, the construction of domestic law on maritime security has undergone three phases: slow development, formation and refinement. Although the rule of law in the seas has been constantly improved, it has provided essential safeguards for maintaining China’s maritime sovereignty, security, and rights and interests. It has facilitated the development of maritime undertakings. However, it still faces problems such as the lack of an explicit constitutional basis, the law of the sea is not an independent departmental law, the absence of the fundamental law of the sea, the lack of operability of marine legislation, and the existence of some gaps in marine laws. Given the problems with the current domestic law on maritime security, it is necessary to make improvements in the following areas: adding marine provisions to the Constitution, formulating the fundamental law of the sea and other marine laws, improving local marine laws, and introducing implementing regulations.